Novel Abetalipoproteinemia Missense Mutation Highlights the Importance of the N-Terminal β-Barrel in Microsomal Triglyceride Transfer Protein Function. (October 2015) - Walsh, Meghan T.; Iqbal, Jahangir; Josekutty, Joby; Soh, James; Di Leo, Enza; Özaydin, Eda; Gündüz, Mehmet; Tarugi, Patrizia; Hussain, M. Mahmood
Abstract : Background—: The use of microsomal triglyceride transfer protein (MTP) inhibitors is limited to severe hyperlipidemias because of associated hepatosteatosis and gastrointestinal adverse effects. Comprehensive knowledge about the structure–function of MTP might help design new molecules that avoid steatosis. Characterization of mutations in MTP causing abetalipoproteinemia has revealed that the central α-helical and C-terminal β-sheet domains are important for protein disulfide isomerase binding and lipid transfer activity. Our aim was to identify and characterize mutations in the N-terminal domain to understand its function. Methods and Results—: We identified a novel missense mutation (D169V) in a 4-month-old Turkish male child with severe signs of abetalipoproteinemia. To study the effect of this mutation on MTP function, we created mutants via site-directed mutagenesis. Although D169V was expressed in the endoplasmic reticulum and interacted with apolipoprotein B (apoB) 17, it was unable to bind protein disulfide isomerase, transfer lipids, and support apoB secretion. Computational modeling suggested that D169 could form an internal salt bridge with K187 and K189. Mutagenesis of these lysines to leucines abolished protein disulfide isomerase heterodimerization, lipid transfer, and apoB secretion, without affecting apoB17 binding. Furthermore, mutants with preserved charges (D169E, K187R, and K189R) rescued these activities. Conclusions—: D169V is detrimental because it disrupts an internal salt bridge leading to loss of protein disulfide isomerase binding and lipid transfer activities; however, it does not affect apoB binding. Thus, the N-terminal domain of MTP is also important for its lipid transfer activity. Abstract : Supplemental Digital Content is available in the text.